A fatal pediatric infection with a C1-like subgenogroup enterovirus A71: case study and enterovirus A71 epidemiology in Finland - Nieminen, Tea; Jääskeläinen, Anne J.; Lindh, Erika; Blomqvist, Soile; Savolainen-Kopra, Carita (Frontiers in Virology, 2024)
Enterovirus A71 (EV-A71) is among the most neuropathogenic non-polio enterovirus types and, in rare instances, can lead to severe or even fatal outcomes, particularly in children under 5 years of age. This case study presents clinical and microbiological findings from the initial documented severe pediatric EV-A71 case in Finland, identified in May 2019. The near-complete genome sequence confirms that the EV-A71 strain belongs to the newly identified recombinant C1-like EV-A71 genetic lineage, which emerged in 2015 and has since been circulating in Europe, causing severe cases among children in various European countries. Enhanced environmental surveillance revealed widespread circulation of EV-A71 in Finland in 2019. However, the overall number of EV clinical cases remained lower than in previous years.